Disease trajectories and medical expenditures of older adults with disabilities: insights from China’s long-term care insurance program - Lijun Zeng; Huaicheng Tan; Shujuan Yang; Lisha Hou; Jinhui Wu; Birong Dong; Adam Gordon; Qingyu Dou (BMC Geriatrics)
Abstract Background In China, long-term care (LTC) system has been implemented in recent years to improve the quality of care for older adults. To address healthcare needs of older adults with disabilities, this study investigated the disease trajectory and medical expenditures. Methods This study included older adults aged 65 and above with disabilities, using data from China’s Long-Term Care Insurance (LTCI) program since July 2017. The participants were followed until June 2021. Diagnoses and hospitalization costs were extracted from electronic medical records and the medical insurance system. Disease trajectory networks were constructed by identifying and linking disease pairs with overlapping conditions. Medical expenditures associated with specific diseases were then calculated. Results The study included 30,003 participants with a mean age of 79.6 ± 11.1 years, 57.0% of whom were female. After a mean follow-up of 21 ± 16 months, 17,428 (58.1%) deaths occurred. The diseases with the highest hazard ratios (HRs) included septic shock (HR 3.59, 95% CI, 3.36–3.84), respiratory failure (HR 3.19, 95% CI, 3.05–3.34), sepsis (HR 2.98, 95% CI, 2.80–3.18), malnutrition (HR 2.38, 95% CI, 2.27–2.48), and decubitus ulcer (HR 2.27, 95% CI, 2.14–2.41). Disease trajectories indicated that mortality was closely associated with malnutrition related diseases (anemia, hypoproteinemia, and malnutrition), pneumonia, and organ failure (respiratory failure and heart failure). Among the top 30 diseases leading to frequent hospitalization, intracerebral hemorrhage (47,882.4 CNY), sepsis (37,978.2 CNY), and respiratory failure (25,921.1 CNY) accounted for the highest total medical costs. Conclusions The study revealed that malnutrition and infection-related diseases contributed significantly to mortality among older adults with disabilities, with the latter also driving higher medical costs. These findings could inform updates to LTCI policies by emphasizing adequate nutritional support and strengthened infection prevention measures. Trial registration chictr.org.cn, ChiCTR2100049973, retrospectively registered.